2021
DOI: 10.3390/atmos12091169
|View full text |Cite
|
Sign up to set email alerts
|

The Carbon Emission Reduction Effect of Technological Innovation on the Transportation Industry and Its Spatial Heterogeneity: Evidence from China

Abstract: The carbon reduction effect of technological innovation in the transportation industry is conducive to China’s anticipated realization of carbon neutrality. Therefore, we evaluated carbon emission reduction effect of technological innovation in the transportation industry in China. Based on the panel data of 30 sample provinces in China (excluding Hong Kong, Macao, Taiwan and Tibet) from 2012 to 2018, using the Moran’I index and Getis-Ord Gi index, this paper analyzes the evolutionary trend and spatial autocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…However, existing studies have shown that the relationship between green innovation and GEE is often nonlinear. Chen and Huo [ 61 ] and Shi et al [ 62 ] argue that there is an inverted U-shaped relationship between innovation and carbon emissions. Hu et al [ 63 ] finds that there is a U-shaped relationship between green innovation and green development.…”
Section: Literature Review and Hypothesis Proposalmentioning
confidence: 99%
See 1 more Smart Citation
“…However, existing studies have shown that the relationship between green innovation and GEE is often nonlinear. Chen and Huo [ 61 ] and Shi et al [ 62 ] argue that there is an inverted U-shaped relationship between innovation and carbon emissions. Hu et al [ 63 ] finds that there is a U-shaped relationship between green innovation and green development.…”
Section: Literature Review and Hypothesis Proposalmentioning
confidence: 99%
“…However, due to the long cycle and high risk of scientific and technological innovation, early R&D investment may not be able to be converted into R&D results in time to play the role of driving the city’s green growth [ 35 ]. Moreover, since now company scale expansion and capital recycling have brought certain negative externality to the environmental system, the “rebound effect” of such negative externality is greater than the energy-saving effect brought by technological innovation [ 65 , 66 ], which will increase energy consumption and carbon emissions to some extent, and is not conducive to improving green economic performance [ 61 , 62 ]. Second, when the innovation level exceeds a certain threshold and reaches a high level, the early R&D investment is transformed into a real force to promote companies’ technological improvement and product iteration.…”
Section: Literature Review and Hypothesis Proposalmentioning
confidence: 99%
“…As an intensive transportation mode, ST is essential for breaking the extensive energy-based vicious circle of development by replacing more efficient energy utilization with traditional low-efficiency energy utilization. In this regard, ST contributes greatly to the upgrading of the transportation sector towards a more energy-intensive mode (Baygin et al, 2022;Shi et al, 2021aShi et al, , 2021b. In addition, with the popularization and development of smart public transportation, energy saving can be achieved when users change their daily travel behavior.…”
Section: Baseline Regression Resultsmentioning
confidence: 99%
“…Furthermore, improved innovation can accelerate the aging of sunset industries and promote the rise of emerging industries such as intelligent transportation, which then drive the transformation and upgrading of traditional labor-intensive industries. Based on the development of ST, capital-intensive and technological-intensive industries will become the mainstream (Liu et al, 2021;Shi et al, 2021aShi et al, , 2021bZailani et al, 2014).…”
Section: Mediation Model Resultsmentioning
confidence: 99%
“…The study [31] considers the relationship between symbolic meanings and the choice of electric vehicles in China, which can be an effective expression of consumer identity. An algorithm for selecting a rolling stock for freight transportation based on the specific conditions of a motor transport enterprise was developed and proposed in [32]. The research [5] presents the design requirements for the rolling stock to effectively manage road transportation, considering the assessment of the vehicle dimensions.…”
Section: Introductionmentioning
confidence: 99%